Progress in the treatment of drug-induced liver injury with natural products - Yuan-kai Sun; Ya-fei Zhang; Li Xie; Fan Rong; Xing-yu Zhu; Jing Xie; Huan Zhou; Tao Xu (Elsevier, 2022)
There are numerous prescription drugs and non-prescription drugs that cause drug-induced liver injury (DILI), which is the main cause of liver disease in humans around the globe. Its mechanism becomes clearer as the disease is studied further. For an instance, when acetaminophen (APAP) is taken in excess, it produces N-acetyl-p-benzoquinone imine (NAPQI) that binds to biomacromolecules in the liver causing liver injury. Treatment of DILI with traditional Chinese medicine (TCM) has shown to be effective. For example, activation of the Nrf2 signaling pathway as well as regulation of glutathione (GSH) synthesis, coupling, and excretion are the mechanisms by which ginsenoside Rg1 (Rg1) treats APAP-induced acute liver injury. Nevertheless, reducing the toxicity of TCM in treating DILI is still a problem to be overcome at present and in the future. Accumulated evidences show that hydrogel-based nanocomposite may be an excellent carrier for TCM. Therefore, we reviewed TCM with potential anti-DILI, focusing on the signaling pathway of these drugs' anti-DILI effect, as well as the possibility and prospect of treating DILI by TCM based on hydrogel materials in the future. In conclusion, this review provides new insights to further explore TCM in the treatment of DILI.